Performance Measurement using the Integrated Performance Measurement System Approach - Aziza, Nurul; Suwignyo, Patdono; Makki, Ahmad (Jurnal Teknik Industri, 2019)
As a non-profit organization in education, Senior High School has the responsibility to achieve educational goals. The school is required to have accountability to the public. Performance measurement is needed to determine organizational performance. Performance measurement can also find out the company success in vision and mission. This study aims to measure performance in schools use integrated performance measurement system (IPMS). This method becomes the starting point for setting goals and identifying Key Performance Indicators (KPI). The results of IPMS produced eight objectives and Â 33 KPIs. Objectives performance includes human resources, curriculum, finance, administration, teaching and learning activities, evaluation processes, work programs, and graduation. The results showed 8 KPIs were red, 4 KPIs were yellow, and 11 KPIs were green. This performance measurement model can also be used in other organizations. This performance measurement model is useful for assessing organizational performance.